2020
DOI: 10.5650/jos.ess20081
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Rheological and Sensory Properties of Some Animal Wax Based Oleogels

Abstract: Introduction Wax refers to the mixture of long-chain apolar compounds forming a protective layer on the surface of some plant and animal tissues, algae, fungi and bacteria. Also, there are some mineral waxes originating from fossil sources. Although chemically, a wax is the ester of a longchain acid and a long-chain alcohol, almost all waxes are a heterogeneous mixture of various compounds including hydrocarbons, wax esters, sterol esters, aldehydes, ketones, alcohols, alkanoic acids, terpenes and others. Typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
5
13
0
Order By: Relevance
“…This ratio indicates that these oleogels were also resistant to syneresis. Very similar findings were found previously for the SW and other plant wax oleogels [ 6 , 7 , 10 , 12 , 14 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…This ratio indicates that these oleogels were also resistant to syneresis. Very similar findings were found previously for the SW and other plant wax oleogels [ 6 , 7 , 10 , 12 , 14 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 90%
“…Commercial shortenings are said to have somewhat higher melting temperatures based on their usage purpose [ 16 ]. Spice-flavored oleogels intended to be used as spreadable fat-like preparations in this study showed somewhat higher melting temperatures, similar to almost all of the previous wax oleogels [ 6 , 7 , 12 , 14 , 20 ]. Therefore, the suitability of these new oleogels as spreadable products and consumer attitudes towards them were evaluated by sensory analysis and consumer tests, and are discussed later.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations